To complete the expression \( 14\sqrt{3} - 4\sqrt{\square} = 2\sqrt{\square} \), we first want to isolate the radical term.
Starting from the equation:
\[ 14\sqrt{3} - 4\sqrt{\square} = 2\sqrt{\square} \]
we can add \( 4\sqrt{\square} \) to both sides:
\[ 14\sqrt{3} = 2\sqrt{\square} + 4\sqrt{\square} \]
This simplifies to:
\[ 14\sqrt{3} = 6\sqrt{\square} \]
Next, we isolate \( \sqrt{\square} \) by dividing both sides by \( 6 \):
\[ \sqrt{\square} = \frac{14\sqrt{3}}{6} \]
Simplifying the right side:
\[ \sqrt{\square} = \frac{7\sqrt{3}}{3} \]
Now, to get \( \square \), we square both sides:
\[ \square = \left(\frac{7\sqrt{3}}{3}\right)^2 \]
Calculating the square:
\[ \square = \frac{49 \cdot 3}{9} = \frac{147}{9} = \frac{49}{3} \]
Thus, completing the expression yields:
\[ \square = \frac{49}{3} \]
So the full expression is:
\[ 14\sqrt{3} - 4\sqrt{\frac{49}{3}} = 2\sqrt{\frac{49}{3}} \]